Satu Dekade IFRS dan Relevansi Nilai Laba pada 50 Biggest Market Capitalization - Wiwin Juliyanti (Universitas PGRI Madiun, 2023)
This study aims to examine whether the convergence of the International Financial Reporting Standards (IFRS) can increase the Value Relevance of earnings on the financial statements of companies listed on the Indonesia Stock Exchange (ISE). This study covers the period before the IFRS convergence (pre- IFRS) in 2010 and after the IFRS convergence (post-IFRS) in 2019. The research sample is a public company that is included in the 50 largest market capitalization, 50 biggest trading frequencies, 50 biggest trading volumes, and 50 biggest trading values. The study was conducted by comparing the adjusted R square value in multiple linear regression models in the period before and after IFRS, and comparing the adjusted R square value between net income and comprehensive income after IFRS. The results of the study prove that there is an increase in the relevance of the value of earnings after the implementation of IFRS and comprehensive income has a value relevance that is higher than net income. The results of the study prove that there is an increase in the relevance of the value of earnings after the implementation of IFRS and comprehensive income has a value relevance that is higher than net income.